Pelaksanaan Psikososial Berbasis Budaya Lokal Sebagai Upaya Pemulihan Trauma PascaGempa Cianjur - Fitria Nurulaeni; Rizqi Ardiansyah; Sundari Sundari; Ujang Nurzaman; Zulfatul Amalia (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
This service aims to help trauma recovery after the Cianjur earthquake, precisely in Cibulakan Village, Cugenang District, Cianjur Regency. In this activity, children become the focus of devotion because they are considered the most vulnerable victims. They lose the environment that should be a daily life to grow and develop, so this underlies the importance of this devotion so that these children can still live their lives as before. The service is carried out by carrying out psychological handling efforts in the form of trauma healing through psychosocial activities based on local culture based on the results of initial observations that have been carried out previously supported by information that shows that children in the village like games, especially traditional games. The result of this devotion is that the enthusiasm and enthusiasm of the children grow again and their joy in living daily life begins to return to normal, even though previously they were faced with very stressful circumstances and even destroyed their mentality.